Compressive Behavior of Some Balls Manufactured by 3D Printing from Ceramic–Polymer Composite Materials - Adelina Hrițuc; Vasile Ermolai; Andrei Marius Mihalache; Liviu Andrușcă; Oana Dodun; Gheorghe Nagîț; Marius Andrei Boca; Laurențiu Slătineanu (Micromachines, 2024)
It is known that ceramic–polymer composite materials can be used to manufacture spherical bodies in the category of balls. Since balls are frequently subjected to compression loads, the paper presents some research results on the compression behavior of balls made of ceramic composite materials with a polymer matrix. The mathematical model of the pressure variation inside the balls highlights the existence of maximum values in the areas of contact with other parts. Experimental research was carried out on balls with a diameter of 20 mm, manufactured by 3D printing from four ceramic–polymer composite materials with a polymer matrix: pottery clay, terracotta, concrete, and granite. The same ceramic–polymer composite material was used, but different dyes were added to it. A gravimetric analysis revealed similar behavior of the four materials upon controlled heating. Through the mathematical processing of the experimental results obtained by compression tests, empirical mathematical models of the power-type function type were determined. These models highlight the influence exerted by different factors on the force at which the initiation of cracks in the ball materials occurs. The decisive influence of the infill factor on the size of the force at which the cracking of the balls begins was found.